Incorporation of nano-materials in cement composite and geopolymer based paste and mortar – A review - Sumesh, M.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Mo, Kim Hung; Alnahhal, M.F. (Elsevier, 2017)
The summary of developments in partially replaced cement composite and geopolymers by industrial by-products are presented along with different nano-materials. Many significant correlations have been studied on association with the better understanding of the interfacial transition zone, microstructural performance, mix design characteristics, setting behavior, mechanical properties, durability and bond strength. The effects of various particle size and different types of nano-materials and their optimal level of replacement have been reviewed on cement composite and geopolymer products. Application of nano-materials in both partially replaced cement composite and geopolymers has significant benefits towards the performance of mortar and paste. The health related issues on using nano-materials and methods can be used to overcome the risks of exposure have been discussed.